Post Comisión de la Verdad: expresiones artísticas y emergencia de sentidos (Tema Central) - Solís Ch., María L. Cristina (2019)
In 2007 a Truth Commission (CVE initials in spanish) was created in Ecuador with the objective of investigating facts that violated human rights that occurred during the period 1984-2008, as well as formulating reparation, judicialization and institutional reforms policies. During its investigation, the CVE incorporated as sources of information both testimonies of victims and / or their relatives as declassified documentation from archives of military and police institutions, as well as some documented complaints from the Comisión Ecuménica de Derechos Humanos (CEDHU). The process unleashed by the CVE gave way to processes for formulating policies aimed at judicialization and reparation, but it also gave way to the emergence of other actions and diverse expressions -which went beyond legal and institutional boundaries- favoring the appearance of a shared scenario between convergent and dissident memories of a past of political violence, the latter offer alternative views to the official one.